LIPID PROFILE IN CHILDREN WITH RHEUMATOID ARTHRITIS - E.Yu. Gudkova; E.I. Alexeeva; G.F. Gordeev (Вопросы современной педиатрии, 2008)
Lipid composition in children with different types of juvenile arthritis was investigated in this trial. Significant decrease of plasma concentration of cholesterol in high density lipoproteins in patients with high activity of rheumatoid arthritis was discovered. «Atherogenic» shift of lipid composition and increase of atherogenity index was shown in most of pediatric patients with different types of juvenile arthritis. The number of children with increased atherogenity index grows according to the increase of disease activity. pediatric patients with high activity of juvenile arthritis and juvenile ankylosing spondylitis are the risk group of early atherosclerosis development.Key words: juvenile arthritis, atherosclerosis, high density lipoproteins, triglyceride, atherogenity index.